P2Y12 receptor inhibitors in patients with non-ST-elevation acute coronary syndrome in the real world: use, patient selection, and outcomes from contemporary European registries - Clive Weston (European Heart Journal - Cardiovascular Pharmacotherapy, 2016)
Non-ST-elevation acute coronary syndrome (NSTE-ACS) is present in about 60–70% of patients admitted with ACS. This study provides a ‘real-life’ overview of NSTE-ACS patient characteristics, dual antiplatelet therapy, and outcomes at both the time of discharge from hospital and up to 1-year post-discharge.10 registries (including 84 054 NSTE-ACS patients) provided data on patient characteristics and outcomes, and 6 of these (with 52 173 NSTE-ACS patients) also provided more specific data according to P2Y12 receptor inhibitor used. Unadjusted analyses were performed at the study level, and no formal meta-analysis was performed due to large heterogeneity between studies in the settings, patient characteristics, and outcome definitions. All-cause death rates across registries ranged from 0.76 to 4.79% in-hospital, from 1.61 to 6.65% at 30 days, from 3.66 to 7.16% at 180 days, and from 3.14 to 9.73% at 1 year. Major bleeding events were reported in up to 2.77% of patients while in hospital (in seven registries), up to 1.08% at 30 days (data from one registry only), and 2.06% at 1 year (one registry).Conclusions There were substantial differences in the use of and patient selection for clopidogrel, prasugrel, and ticagrelor, which were associated with differences in short- and long-term ischaemic and bleeding events.